Evolution of brain tumor growth model: a back-in-time approach - Aboaba, Abdulfattah A.; Hameed, Shihab A.; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha; Harun, Rahmat H.; Mohd Zain, Norzaini Rose (2012)
One of the crucial stages in Image Guided Surgery (IGS) protocol is the IGS planning stage, the major requirements at that stage are to determine tumor extent and size by reconstructing tumor slices, and to determine the best way to approach affected site. The surgeon is clinically responsible to do these with the aid of IGS software that is fashioned in line with the surgeon training. It has been observed that lots of time used at that stage could be saved if a good model that will accurately estimate tumor growth from few slices could be developed to assist at that stage. This paper presents a tumor growth modeling approach based on step response of electrical energy devices, and its application to tumor estimation using non-IGS protocol image slices to produce tumor area estimation that is comparable for image reconstruction purposes with tumor area found on the thin slice IGS protocol images, thereby eliminating the need for time consuming IGS protocol imaging.